Analysis of Mosque Financial Management Systems in an Islamic Economic Perspective (Case Study of the Palampang Jami Mujahidin Mosque, Pangkep Regency) - Andi Muh. Bintang (Pustaka Digital Indonesia, 2024)
This research aims to (1) determine and analyze the financial management system of the Jami Mujahidin Palampang Mosque, Pangkep Regency from an Islamic economic perspective and (2) to determine the supporting and inhibiting factors for implementing financial management at the Jami Mujahidin Palampang Mosque, Pangkep Regency. The type of research used is descriptive qualitative. The results obtained in this research are (1) The financial management system of the Jami Mujahidin Palampang Mosque, Pangkep Regency, namely in the form of mosque cash sources, activity budgeting, and financial traffic. Looking from the perspective of Islamic accountability in the financial management of the Jami Mujahidin Palampang Mosque, Pangkep Regency, based on the concepts of caliphate, justice and trust in general it has been carried out well even though the ideal has not been fully fulfilled; (2) The supporting factor in this research is the congregation's enthusiasm for donating and participating in every mosque activity. Meanwhile, the inhibiting factor is the negative perception from several parties in the local community who think that the mosque management is not open enough in terms of financial management. The next inhibiting factor is that many mosque administrators are less active in carrying out their mandate and only a few administrators are active. This research recommendation is intended for mosque administrators, congregations, and the government